Lost birds - Hillerman, Anne, 1949- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2024)
Retired from the Navajo Tribal Police, P.I. Joe Leaphorn is hired to find the birth parents of a woman raised by a bilagaana family, which unexpectedly turns into a complicated case, while Officer Bernadette Manuelito investigates an explosion linked hisinvestigation.
Keywords: Leaphorn, Joe, Lt. (Fictitious character) -- Fiction; Chee, Jim (Fictitious character) -- Fiction; Manuelito, Bernie -- (Fictitious character) -- Fiction; Police -- New Mexico -- Fiction; Navajo Indians -- Fiction; Detective and mystery fiction; Novels